Análise de fraturamentos para determinação de áreas instáveis na faixa de dutos Osvat/Osplan - São Sebastião, em São Paulo - De Moura, Cristiane Alessandra [UNESP]; De Mattos, Juércio Tavares [UNESP]; Jiménez-Rueda, Jairo Roberto [UNESP] (My University, 2012)
The present work aimed at characterizing geological features that identify areas with high ruptibility (fracturing) in the Osvat/Osplan pipeline in São Sebastião, São Paulo. The analysis of ruptile geological structures (lines of strikes and structural lineaments) through the use of orbital remote sensing was used as systematic mapping. The analysis of these features enables the inference of factors, such as permeability, infiltration and degree of shear in the region, factors which influence the processes of erosion and landslides in the area. On the map of structural lineaments, points of lineaments intersection from different directions were analyzed, followed by the counting of the frequency of these items per unit area, allowing the statistical modeling of spatial distribution, generating the map of density of structural lineament intersections, which allows determining areas with the highest percolation of fluid in the rock structure. However, on the map of lines of strikes, a space analysis was conducted to identify the two directions with higher frequency of lines of strikes in order to establish the maximums 1 and 2 and to identify the areas of abrupt changes of direction of these strike lines. In such areas where abrupt changes of directions of maximum lines of strikes occur, consequently there will be intense percolation of fluids, responsible for higher alterability of the rock/soil complex, facilitating the installation of erosion processes and landslides, increasing the area instability and consequently the vulnerability of the pipeline.
Analysis of fracturing to determine areas of instability in the strip of intervention of the Osvat/Osplan pipeline in São Sebastião, state of São Paulo
Keywords: Analysis of fracturing; Physical environment and pipelines; Satellite images